PARTIAL DISCHARGE ANALYSIS ON PRINTED CIRCUIT BOARDS USING CURRENT TRANSFORMER SENSOR FOR INSULATION PERFORMANCE EVALUATION - Muhammad Kodrat; Imam Syafi’e; Ekki Kurniawan; Jangkung Raharjo (TESLA: Jurnal Teknik Elektro, 2026)
The rapid development of modern power electronics systems at the 20 kV medium-voltage level demands high reliability of printed circuit board (PCB) insulation. Under medium-voltage conditions, PCB insulation materials are susceptible to partial discharge (PD) activity, particularly in areas with non-uniform electric field distribution, which can accelerate insulation failure and reduce system reliability. This study examines the insulation performance of medium-voltage PCBs through PD measurements using non-invasive current transformer (CT) sensors that do not damage the equipment. The proposed approach utilizes time-domain PD analysis to detect impulse current signals generated by PD activity without modifying the PCB insulation structure. Key parameters such as pulse magnitude, rise time, pulse width duration, and PD fall time are analyzed to characterize PD activity. Additionally, PD waveform analysis is performed to evaluate discharge characteristics and their correlation with PCB insulation conditions. The novelty of this research lies in the application of CT sensors as a method for evaluating PCB insulation in medium-voltage power electronics applications. The research results show that the proposed method is capable of detecting low-level PD activity and provides relevant diagnostic information for PCB design development and insulation condition monitoring strategies in medium-voltage power electronics systems Abstrak Perkembangan pesat sistem power electronics modern pada skala tegangan menengah 20 kV menuntut keandalan isolasi printed circuit board (PCB) yang tinggi. Pada kondisi tegangan menengah, material isolasi PCB rentan terhadap aktivitas partial discharge (PD), khususnya pada daerah dengan distribusi medan listrik yang tidak seragam, yang dapat mempercepat terjadinya kerusakan insulasi dan menurunkan keandalan sistem. Penelitian ini mengkaji performa isolasi PCB tegangan menengah melalui pengukuran PD menggunakan sensor current transformer (CT) yang bersifat non-invasif/tanpa merusak peralatan. Pendekatan yang diusulkan memanfaatkan analisis PD pada domain waktu untuk mendeteksi sinyal arus impuls yang dihasilkan oleh aktivitas PD tanpa memodifikasi struktur isolasi PCB. Parameter utama seperti magnitudo pulsa, waktu naik, durasi lebar pulsa, dan waktu turun PD dianalisis untuk mengkarakterisasi aktivitas PD. Selain itu, analisis bentuk gelombang PD dilakukan untuk mengevaluasi karakteristik pelepasan dan keterkaitannya dengan kondisi isolasi PCB. Kebaruan penelitian ini terletak pada penerapan sensor CT sebagai metode evaluasi isolasi PCB pada aplikasi power electronics tegangan menengah. Hasil penelitian menunjukkan bahwa metode yang diusulkan mampu mendeteksi aktivitas PD level rendah dan memberikan informasi diagnostik yang relevan untuk pengembangan desain PCB dan strategi pemantauan kondisi isolasi pada sistem power electronics tegangan menengah.